Specific Language Impairment: Defining the Disorder and Identifying Its Symptoms in Preschool Children - Chia, Noel Kok Hwee (Journal of the American Academy of Special Education Professionals, 2014)
The aim of this short paper is three fold: Firstly, it is to define Specific Language Impairment (SLI) and to identify the various symptoms of the disorder so as to establish a better understanding of these children through interaction with them, their parents, and other allied professionals, and how to go about designing an appropriate lesson to work with such children. Secondly, it introduces SLI within the Triple-D framework which encompasses Diagnostics (which includes screening, assessment and evaluation), Dialogics (collaborative consultation and counseling) and Didactics (design of an intervention program and implementation of the program). It also touches briefly on the current application of the Triple-D framework in the early intervention program for preschool children with SLI carried out by early childhood educators in Singapore. Thirdly, this paper will illustrate with an example how to design an action lesson plan incorporating simple strategies to be used with such children.